2022
DOI: 10.1177/20438087221090350
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of early night sleep effects on subsequent fear extinction learning and recall

Abstract: Extinction learning is considered an important underlying process of successful treatment of posttraumatic stress disorder (PTSD). However, sleep disturbances may impede this learning process: Current accounts postulate that sleep facilitates encoding by promoting neural plasticity during slow wave sleep (SWS). Based on this hypothesis, we tested whether early night sleep, with high amounts of SWS, facilitates subsequent extinction learning and recall. Sixty-three participants took part in a trauma-adapted fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…This finding aligns with research in humans showing that sleep deprivation after fear conditioning results in poor extinction memory 61,62 . Moreover, a recent study observed a positive relationship between the quantity of REM sleep preceding extinction learning and the strength of extinction memory in humans 63 . Likewise, studies in rats reported worse extinction memory when performing REM deprivation after conditioning in both cued and contextual fear tasks 64 .…”
mentioning
confidence: 96%
“…This finding aligns with research in humans showing that sleep deprivation after fear conditioning results in poor extinction memory 61,62 . Moreover, a recent study observed a positive relationship between the quantity of REM sleep preceding extinction learning and the strength of extinction memory in humans 63 . Likewise, studies in rats reported worse extinction memory when performing REM deprivation after conditioning in both cued and contextual fear tasks 64 .…”
mentioning
confidence: 96%